The effect of the burn wounds dressing and mechanical debridement training package on nursing interns’ knowledge and executive functions: A quasi-experimental study - Manizhe Otaghi; Mohamadreza Bastami; Yousef Veisani; Hamid Taghinejad; Alireza Vasiee; Arman Azadi (Journal of Research Development in Nursing and Midwifery)
Background: Despite receiving training on caring for burn wounds in the undergraduate nursing program, nursing students do not acquire enough knowledge and skills in wound dressing and debridement. This research was carried out to determine the effect of a training package on the nursing interns’ knowledge and executive functions regarding the dressing and mechanical debridement of burn wounds. Methods: This quasi-experimental study was conducted on 60 nursing internship students in their 7th semester in Ilam, Iran, in 2023. A convenience sampling method was used, and participants were randomly assigned to groups using dice-throwing for simple randomization. Over six weeks, the intervention group received training on dressing burn wounds through a learning package, virtual gamification, a simulator, and clinical and real exercises. The control group received routine content through oral education by the same lecturer. Knowledge and executive function in mechanical debridement of burn wounds were assessed using the KMDBWT and EFMDBWT tools before and two weeks after the intervention. Data were analyzed with a standard error of 0.05 using Kolmogorov-Smirnov, independent t, paired t, chi-square, and analysis of covariance tests by SPSS V.16. Results: Before the intervention, no significant difference was observed between the mean and standard error of the control and intervention groups' knowledge and executive performance scores. However, after the intervention, the knowledge scores significantly increased in the intervention group (16.35 ± 0.288) compared to the control group (10.00 ± 0.356) (P=0.001). Moreover, after the intervention, the executive function scores in the intervention group (105.00 ± 0.939) were significantly increased compared to the control group (56.81 ± 0.738) (P=0.001). Conclusion: The burn wound dressing and mechanical debridement training increased nursing students' knowledge and executive function. Hence, this educational package is recommended as a supplementary teaching resource.